MAKNA HIDUP DI TENGAH KETIDAKPASTIAN ZAMAN MODERN: REFLEKSI TEOLOGIS ATAS KITAB PENGKHOTBAH TENTANG PENCARIAN ARTI KEHIDUPAN - Yustinus Ramli Pan; Yasinta Rahmawati; Adrianus Jebarus (Adisam Publisher, 2026)
This study aims to examine the meaning of life in the midst of modern uncertainty through a theological reflection on the Book of Ecclesiastes and its relevance in light of Catholic Church teachings. The method used is library research with a descriptive-analytical approach, analyzing the text of Ecclesiastes, official Church documents, and relevant theological literature. The results show that the Book of Ecclesiastes honestly portrays human life as marked by vanity (hebel), limitations, and uncertainty. However, it also affirms that the meaning of life can be found in fearing God, enjoying life’s simple blessings, and living with moral responsibility before God. The teachings of the Catholic Church complement this reflection by emphasizing that the true meaning of life is rooted in a relationship with God, hope for salvation, and a life lived in love and truth. Therefore, in the midst of modern uncertainty, human beings can still discover an authentic meaning of life through faith, hope, and a life oriented toward God.